Promoting development of entrepreneurial skills of youth in Ghana through a structured sport intervention program - Ocansey, Reginald Tetteh-Ahumah; Nyawornota, Vida Korleki; Adamba, Clement; Tay, Doris Akosua; Musah, Karim; Nyanyofio, Oscar Cornelius Nyanyo; Malete, Leapetswe; McCole, Daniel (Frontiers in Education, 2023)
The purpose of this brief report is to describe how a structured sport-based positive life skills program can be used in promoting the development of entrepreneurial skills of youth specifically in Ghana following the two three-country publications by Malete et al., 2021 and McCole et al., 2022. A total of 29 youth participated in the study with 11 as the control group and the remaining 18 as the intervention group. The students in the intervention together with 5 parents participated in a weekend mapping camp. Data was collected with the Youth Experience Survey for Sport (Sullivan et al., 2015) to measure the Life skills and entrepreneurship skills using a quasi-experimental pre-post-test control group design. The youth in the intervention group reported important physical and personal benefits and entrepreneurial skills such as cooperation (teamwork), risk-taking, creativity, leadership, cognitive development, and positive engagement in physical activity which they did not previously have. The results are similar to those from the two previously published papers by Malete et al,. 2022 and McCole et al., 2022 giving this report a promising validity and reliability. Similar to the previously published three-country research papers, the perceived gains in this report also show that exposing youth to a structured sport-based positive life skills program produce both physical benefits and development of lifelong skills necessary to develop mindsets necessary for entrepreneurial endeavors. When this intervention is upscaled in Ghana the country could offset high youth unemployment with its associated challenges.